2006
DOI: 10.1007/s00125-006-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic polymorphisms of SLC2A10 gene and type 2 diabetes in the Taiwanese population

Abstract: Aims/hypothesis:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…GLUT10 has received special interest because it is located at human chromosomal region 20q12-13.1, which has been linked to a susceptibility loci for Type 2 diabetes. However, polymorphisms of GLUT10 are not associated to Type II diabetes in Caucasian Americans [67], Danish [68] and Taiwanese populations [69], but GLUT10 deficiency has recently been found to be associated with human arterial tortuosity syndrome [70].…”
Section: Glut10 (Slc2a10)mentioning
confidence: 99%
“…GLUT10 has received special interest because it is located at human chromosomal region 20q12-13.1, which has been linked to a susceptibility loci for Type 2 diabetes. However, polymorphisms of GLUT10 are not associated to Type II diabetes in Caucasian Americans [67], Danish [68] and Taiwanese populations [69], but GLUT10 deficiency has recently been found to be associated with human arterial tortuosity syndrome [70].…”
Section: Glut10 (Slc2a10)mentioning
confidence: 99%
“…Previously, a region on chromosome 20q13 containing SLC2A10 has been linked to type 2 diabetes mellitus [Ghosh et al, 1999;Klupa et al, 2000], and SLC2A10 was suggested as a good candidate gene [Andersen et al, 2003;Bento et al, 2005;Lin et al, 2006;McVie-Wylie et al, 2001;Mohlke et al, 2005;Rose et al, 2005]. Evaluation of glucose metabolism in patients harboring pathogenic SCL2A10 mutations could elucidate whether this association with diabetes mellitus exists.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility noted, is that lower expression and activity of the two ABC genes may be caused by hyperglycemia in T2DM. Though unproven, the point is supported by expression levels of ABCA1 inversely comparing to expression levels in leukocytes of glucose deprived fasting individuals without T2DM or hyperglycemia [26][27][28]. An analysis of a Mexican population with T2DM indicated single nucleotide polymorphisms (SNP) in ABCA1 associated with those with T2DM, with a dbSNP location of rs9282541, as well as four other locations in the analysis [29].…”
Section: Atp Binding Cassette (Abc) Transportersmentioning
confidence: 99%